(untitled) (Journal of the College of Basic Education, 2026)
This study examines the productivity of Event Structure in the verbs found in Imam Ali’s (peace be upon him) Sermon on Jihad, through the application of Semantic Roles Theory developed by Charles Fillmore. The research focuses on identifying the main semantic roles (such as agent, theme, experiencer, instrument, etc.) and analyzing the morphological and semantic structure of the verbs within their rhetorical context. The findings reveal significant variation in verb forms, including past, present, and imperative tenses—which contribute to shifts in their event structure. The deliberate use of both active and passive voice further enhances the emotional and persuasive impact on the audience. The distribution of semantic roles indicates a dominance of verbs as directive tools within the sermon, as Imam Ali (peace be upon him) strategically employed them to convey meanings ranging from encouragement and reproach to advice and warning. The study affirms that the event structure (verbs) in the sermon serves not only linguistic functions but also acts as a powerful semantic tool in shaping the ideological and emotional stance, reflecting Imam Ali’s (peace be upon him) vision of concepts such as jihad, abandonment, and support